Abnormal Returns and Trading Volume in the Indonesian Stock Market in Relation to the Presidential Elections in 2004, 2009, and 2014 - Imelda, Imelda; Siregar, Hermanto; Anggraeni, Lukytawati (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2015)
Presidential election is considered as relevant information for stock market’s investors to make investment decision. The objective of this study is to examine differences in average abnormal return and trading volume activity on sectoral indices’ stocks before and after the presidential elections in 2004, 2009, and 2014. The research uses the event study method. The data are collected from the Indonesia Stock Exchange. The daily closing prices on sectoral indices used in this study consist of 120 days preceding and 30 days succeeding the elections. There is a strong evidence of differences in average abnormal return on Indonesian’s sectoral stock market before and after the presidential elections especially for the mining sector. However, the trading volume activities of the Indonesian’s sectoral stock market before and after the elections were statistically the same. The litigation from the last election results had no impact on most Indonesian’s sectoral stock, except for the financial as well basic industry and chemical sectors. The analysis concludes that the trade, services, and investment are the most stable sectors, while mining is the opposite one.